INBORN ERRORS OF METABOLISM AND METABOLIC WORK-UP IN AUTISM SPECTRUM DISORDERS - Anja Krivec Penič; Živa Prijatelj; Manca Ločičnik; Mojca Žerjav Tanšek (The Society for Children with Metabolic Disorders, 2021)
Autism spectrum disorders are complex developmental dis-orders characterised by disturbances in social interactions, verbal and non-verbal communication and imagination. The frequency of autism spectrum disorders has markedly increased in recent years. The cause of autism spectrum dis-orders is still unknown, but they are most likely triggered by the interaction between genetic and environmental inﬂuences. Inborn errors of metabolism are one of the genetic causes in the diagnostics of autism spectrum disorders and are present in 2-5% of children with this condition. An autism spectrum disorder and developmental regression with additional clinical signs and symptoms may indicate an inborn error of metabolism as the aetiology. An individual and targeted approach with metabolic and genetic diagnostic work-up is needed to conﬁrm the metabolic cause. In the future, the diagnostic work-up for autism will be based on genetics, probably as early as the prenatal period, especially if genetic treatments for some monogenetic causes of metabolic disorders would become available. The recommendations for the metabolic work-up for inborn errors of metabolism in patients with syndromic autism are reviewed in this article. The case report of a child with lysosomal storage disease and autism validates the importance of a timely diagnosis in this group of the patients.